Structure of the upper mantle of the territory of the Kyrgyz Republic according to seismological data (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article was received obtained seismic tomographic models of the upper mantle of the territory Kyrgyz Republic and adjacent territories according to data from strong teleseismic earthquakes. Velocity inhomogeneities were obtained using three different algorithms seismic tomography. The structural features of the lowest part are analyzed crust and upper mantle of the Kyrgyz part of the Tien Shan and adjacent territories.